Cell reprogramming shapes the mitochondrial DNA landscape - Wei Wei (Nature Portfolio, 2021)
Here the authors describe high depth mitochondrial DNA (mtDNA) sequence analysis of 146 human induced pluripotent stem cell (hiPSC) lines as well as single cell RNA-seq (scRNAseq) of hiPSCs undergoing differentiation from 125 donors; reporting mtDNA diversity and some variants favoured after reprogramming.